2003
DOI: 10.1034/j.1600-0897.2003.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenases in Pregnancy II: HO‐2 is Downregulated in Human Pathologic Pregnancies

Abstract: Our data indicate that HOs play a crucial role in pregnancy and low expression of HO-2, as observed in pathologic pregnancies, may lead to enhanced levels of free heme at the feto-maternal interface, with subsequent upregulation of adhesion molecules, allowing enhanced inflammatory cells migration to the feto-maternal interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
62
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 61 publications
6
62
0
Order By: Relevance
“…These data on up-regulated HO-1 after Co-PP treatment nicely support findings from other groups in transplanted organs (16). HO-2 was not found to be up-regulated after Co-PP in other tissues; however, we already reported that HO-2 can be up-or down-regulated at the fetal-maternal interface (9,10,18). These data on augmented HO-2 protein expression at the fetal-maternal interface suggest that HO-2 is being differently regulated at the fetal-maternal interface than in other tissues.…”
Section: Co-pp Application Up-regulated Ho-1 Expression At the Fetalmsupporting
confidence: 78%
See 1 more Smart Citation
“…These data on up-regulated HO-1 after Co-PP treatment nicely support findings from other groups in transplanted organs (16). HO-2 was not found to be up-regulated after Co-PP in other tissues; however, we already reported that HO-2 can be up-or down-regulated at the fetal-maternal interface (9,10,18). These data on augmented HO-2 protein expression at the fetal-maternal interface suggest that HO-2 is being differently regulated at the fetal-maternal interface than in other tissues.…”
Section: Co-pp Application Up-regulated Ho-1 Expression At the Fetalmsupporting
confidence: 78%
“…Furthermore, boosting abortion with sonic stress or IL-12 application down-regulated the HO-1 and HO-2 expression at the murine fetal-maternal interface (9). Interestingly, HO-1 and HO-2 were also down-regulated at the fetal maternal interface from patients undergoing spontaneous abortion during the first trimester, as compared with age-matched women undergoing normal pregnancies (18).…”
mentioning
confidence: 96%
“…This is strongly supported by the demonstration that biliverdin administration rescued the impaired inflammatory and reparative response of the HO-2-null mice; it accelerated wound repair, promoted resolution, and attenuated neovascularization. It is noteworthy that HO-2 expression levels have been shown to decrease significantly in human pathologies and conditions that are associated with chronic inflammation such as preeclamptic pregnancies 5,50 and prolonged cigarette smoking. 6 Hence, it is not unreasonable to speculate that there is a causal relationship between the levels of HO-2 expression and activity and unresolved chronic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is an inducible enzyme, whereas HO-2 displays, in general, a constitutive expression that is developmentally regulated 4 and is altered in human pathological conditions. 5,6 HO-1 and HO-2 are alike in terms of mechanisms of heme oxidation, co-factor and substrate specificity, and susceptibility to inhibition by porphyrins. 2,7 They differ in their postulated function: whereas HO-2 is believed to function as the constitutive HO activity contributing to cell homeostasis, HO-1 expression is relatively low in most tissues, and its significance comes to light in response to injury.…”
mentioning
confidence: 99%
“…Importantly, HO-2 expression is decreased in endothelial cells from preeclamptic and fetal growth-restricted placentas (4). Lastly, HO-2 expression is decreased in synctiotrophoblasts and invasive trophoblasts from third-trimester preeclamptic patients (29). These seminal studies illustrate that HO-2, the constitutively expressed enzyme, may play a role in the pathophysiology of preeclampsia.…”
Section: Discussionmentioning
confidence: 95%